Electronic Medical Record: Challenges in Terms of Management Elements Related to The Implementation of Inpatient Electronic Medical Records - Insani, Tria Harsiwi Nurul; Wikansari, Nurvita; Febrian, Ehci (Universitas Muhammadiyah Sidoarjo, 2024)
Patient medical records began to switch to an electronic basis with the issuance of Minister of Health Regulation Number 24 of 2022 concerning Medical Records. This policy regulates health service facilities to run an electronic patient medical history recording system. The transition process will be carried out no later than 31 December 2023. Hospitals are one of the health service facilities that are required to maintain electronic medical records. It is important to assess readiness before implementing electronic medical records, to optimize its implementation. This research aims to analyze the challenges of implementing inpatient EMR at the PKU Muhammadiyah Bantul Hospital which will be reviewed from management elements, namely Man, Method, Machine, Material, and Information. This research carried out in the early 2023. The type of research used is descriptive research with a qualitative approach, to explore or obtain comprehensive, broad, and in-depth information regarding the challenges of implementing inpatient electronic medical records in terms of management elements. The result of this study; the challenge of implementing EMR from the Man element; there are found officers who do not have an educational background in medical records or are not qualified as medical recorders. Money; The hospital's operational cost budget is obtained from the hospital itself and funds for implementing inpatient electronic medical records are already available, so there are no obstacles to the budget for implementing the EMR. Method; Hospital does not have yet an SOP or proedure, especially for implementing inpatient EMR. Machine; facilities such as computers or PCs in each ward still need to be added. Material; Inpatient EMR materials are still in the development stage and are built by the hospital itself without any collaborating (third-party) vendors or teams. Information; Hospital has not conducted external training and outreach to medical staff who will use EMR in the inpatient unit. Conclusion, The hospital still has several obstacles such as in terms of man, method, machine, material, and information but there are no difficulties with money so it is necessary to increase the time allocation for implementing inpatient EMR.